Identifying thermogenic and microbial methane in deep water Gulf of Mexico Reservoirs. (15th April 2020) - Thiagarajan, Nivedita; Kitchen, Nami; Xie, Hao; Ponton, Camilo; Lawson, Michael; Formolo, Michael; Eiler, John
Abstract: The Gulf of Mexico (GOM) produces 5% of total U.S. dry gas production (USEIA, 2016 ). Despite this, the proportion of microbial and thermogenic methane in discovered and producing fields from this area is still not well understood. Understanding the relative contributions of these sources in subsurface environments is important to understanding how and where economically substantial amounts of methane form. In addition, this information will help identify sources of environmental emissions of hydrocarbons to the atmosphere. We apply stable isotopes including methane clumped-isotope measurements to solution and associated gases from several producing fields in the U.S. Gulf of Mexico to estimate the proportions, properties and origins of microbial and thermogenic endmembers. Clumped isotopes of methane are unique indicators of whether methane is at thermodynamic isotopic equilibrium or affected by kinetic processes. The clumped methane thermometer can provide insights into formation temperatures and/or into kinetic processes such as microbial methanogenesis, early catagenetic processes, mixing, combinatorial processes, and diffusion. In this data set, we find that some fluids have clumped isotope methane apparent temperatures consistent with the methane component being produced solely by the thermogenic breakdown of larger organic molecules at substantially greater temperatures than those reached in shallow reservoirs. A portion of these reservoirs with hot clumped isotope methane temperatures are consistent with exhibiting a kinetic isotope effect. Other reservoirs have clumped isotope methane apparent temperatures, and other isotopic and molecular proportions, consistent with mixtures of microbial and thermogenic methane. We show that in certain cases the evidence is most consistent with formation of the microbial methane in the current reservoir. However, in other cases the methane is produced at significantly shallower depths and is then transported to greater depths as a result of post generation burial of methane bearing sedimentary sequences to the current reservoir conditions. For the first time, we show that methane of an unambiguously purely microbial origin (i.e. those that do not contain obvious contributions of thermogenic methane) is dominantly generated at temperatures less than 60 °C, despite burial to greater depths. This finding suggests that, while microorganisms are able to generate methane at temperatures up to 105 °C under laboratory conditions (Brock, 1985), in the Gulf of Mexico, microbial methane is dominantly produced in the 20–60 °C window.